UV Irradiation and Ozone Treatment of κ-Carrageenan: Kinetics and Products Characteristics - Aji Prasetyaningrum; Widayat Widayat; Bakti Jos; Yudhy Dharmawan; Ratnawati Ratnawati (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
The low molecular weight (LMW) of sulfated polysaccharides including k-carrageenan, is shows a wide spectrum of biological activities. This research investigates the influence of UV irradiation, ozone (O3), and the combination of O3/UV methods on the depolymerization of k-carrageenan. The depolymerization kinetics of k-carrageenan using the Advanced Oxidation Process (UV/O3) was also studied. Furthermore, the intrinsic viscosity method was used to determine the average molecular weight of the research sample, and a mathematical model was developed to predict the kinetic rate constant, as a function of ozone dosage and UV irradiation intensity. Therefore, the physicochemical and morphological properties of the degraded k-carrageenan were analyzed by FT-IR, SEM, and XRD. The intrinsic viscosity k-carrageenan decreases with increasing UV light intensity and ozone concentration. The combination of UV/O3 treatment appeared to be more effective than the individual approaches, as the highest kinetic rate constant for depolymerization was 1.924×10-4 min-1, using 125 mg/L ozone concentration and 40 mW/cm2 of UV lamp intensity. This research also evaluated the relationship between various experimental conditions, including UV lamp power dissipation and ozone concentration on the reaction kinetics model, and the results suggest that lower effect is contributed by UV irradiation intensity. In addition, FT-IR spectra showed the absence of any significant change in the functional properties of k-carrageenan treated with UV and O3 processes, although the morphological properties of the LMW k-carrageenan were rougher and more porous than the native k-carrageenan. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).